Potentials of Multi-Touch Interactions for Teaching and Learning - Adesina, Adewale Oluwafemi (West African Journal of Open and Flexible Learning, 2026)
There has been a lot of buzz around multi-touch devices since Apple released the iPhone in 2007 and Microsoft unveiled their surface computer the same year. However, many of the applications developed were primarily for games, and not many applications have focused on teaching and learning of key educational concepts. The multi-touch environment can be used to accommodate learners who prefer to learn by doing and enrich the experiences of visual learners, leading to meaningful learning for everyone. B&), alternatives are being sought for the traditional point-and-click systems used for inputs (Bhuiyan and Picking, 2009) because they can be slow and cumbersome to use especially among the elderly (Kendon, 1997). Multi-touch devices are possible replacements. These developments have led to the evolution of different gestures for accomplishing certain tasks on the devices. The need therefore arises for serious applications to be developed using context-specific gestures so that the intuitiveness of solutions and user interface issues can be investigated and standardised. This paper provides an overview of multi-touch hardware, products and markets as well as their uses in education for teaching and learning purposes; it presents a synopsis of the emergence and historical development of multi-touch devices and products li- have become available. It also discusses findings from a group of computer science students who used an iPad to carry out diagramming tasks using an Entity-Relationship diagram modelling tool prototype. Test results showed diagramming tasks to be possible and students' recognition of the potential of such applications in meeting their educational needs.
Keywords: Multi-touch; ICTs; open and distance learning; iPad; gestures; interactivity